A study on psychological implications of COVID-19 on nursing professionals. (2nd January 2021) - Wang, Shuling; Xu, Hua; Kotian, Rahul P.; D'souza, Brayal; Rao, Shreyas Suresh
ABSTRACT: Introduction: The World Health Organization declared COVID-19 as a pandemic on 11 March, 2020, followed by an unprecedented global increase of the disease in recent times. Healthcare workers, including Nursing Professionals (NP), are more likely to experience psychological distress during the pandemic. The purpose of the study is to examine the stress, depression, and anxiety experienced by the nursing professionals in India, who provide care to COVID positive patients. Methods: A cross-sectional, web-based survey collected demographic data and mental health measurements from 187 NPs from 29 April, 2020 to 15 May, 2020. Eligibility criterion was NPs' treating COVID positive patients during the pandemic period. Results: A total of 103 (55.08%) participants were screened positive for depression, 105 (56.14%) for anxiety, and 80 (42.78%) for stress. In addition, 24 (12.83%) participants experienced comorbid conditions, suffering from extremely severe or severe forms of stress-anxiety-depression levels. Conclusion: Participants reported high rates of depression, anxiety, and stress especially frontline NPs directly engaged in providing services for patients with COVID-19. The paper recommends counseling, mentorship, Cognitive Behavioral Therapy, and specialty trainings focused on patient care, as possible interventions for managing the psychological wellness of NPs during these testing times.